Low Subsurface Water Storage Capacity Relative to Annual Rainfall Decouples Mediterranean Plant Productivity and Water Use From Rainfall Variability. Issue 12 (19th June 2019) - Hahm, W. J.; Dralle, D. N.; Rempe, D. M.; Bryk, A. B.; Thompson, S. E.; Dawson, T. E.; Dietrich, W. E.
Abstract: Plant water stress in response to rainfall variability is mediated by subsurface water storage, yet the controls on stored plant‐available water remain poorly understood. Here we develop a probabilistic water balance model for Mediterranean climates that relates the amount of water stored over the wet season to annual rainfall statistics and subsurface storage capacity in soil and weathered bedrock. This model predicts that low storage capacity—relative to winter rainfall—results in similar year‐to‐year summer water availability, as both relatively wet and dry winters replenish storage. Observed water balances in seven catchments in the Northern California Coast Ranges exhibited this dynamic. We hypothesized that plants would be decoupled from precipitation variability at these storage‐capacity‐limited sites and observed that summer productivity and water use (inferred from the enhanced vegetation index) were independent of winter rainfall totals. These areas emerged largely unscathed from recent extreme drought, despite widespread plant mortality elsewhere. Plain Language Summary: When does a shortage of precipitation become a shortage of water supply to plants? In rain‐dominated seasonally dry climates, the answer depends on how water is stored belowground. Here we propose—perhaps counterintuitively—that low water storage capacity in Earth's critical zone (which includes soil and weathered bedrock) relative to average rainfall can decouple plant community productivity and water use from rainfall variability, and conversely that relatively large storage capacity increases plant sensitivity to annual swings in rainfall totals. A simple model and analysis of watersheds in winter wet, summer dry climates in California reveal that where it consistently rains much more than the subsurface can store, a similar amount of water is stored belowground in both relatively wet and dry years, with excess rainfall leaving as runoff. We hypothesized that this would result in similar year‐to‐year summer plant water availability, in spite of highly variable winter rainfall. We found, via satellite observations, that summer plant greenness was insensitive to swings in precipitation at these "storage‐capacity‐limited" sites. Contrary to predictions based primarily on tree density and rainfall deficits, these sites did not experience widespread mortality in the 2011‐2016 extreme drought. Key Points: Where annual rainfall reliably exceeds subsurface storage capacity, plant productivity should be insensitive to rainfall variability Water balances reveal sites where storage is replenished in both wet and dry winters, resulting in consistent summer plant water supply Such storage‐capacity limited sites are inherently resilient to meteorological drought